Teachers perceptions of digital learning: A case study of the learning process at Bahtera Multiple Intelligence Preschool in Bukit Jelutong City, Malaysia - Kurnia Sary; Muqodas, Idat; Nikawanti, Gia; Lily Muliana Mustafa (Jurnal Pendidikan Anak, 2025)
The importance of teachers understanding of technology integration in early childhood education has become one of the key issues in today’s educational environment. The aim of this study is to explore teachers perceptions of the use of digital learning. The subjects of this research are the teachers and the owner of Bahtera Multiple Intelligence Preschool in Malaysia. The instruments used in this study are observation and interviews. Data collection was conducted through in-depth interviews related to digital learning. Data were analyzed using triangulation, coding, and data reduction methods, focusing on the identification of key themes from the interview transcripts. The results of the study indicate that teachers have diverse views on the effectiveness, ease of use, and challenges of digital learning. These perceptions are influenced by the availability of technological resources, training, and the teachers personal preferences regarding learning methods.